Android-Bases Menu Selection Application At Café De One In Giri Kencana Village, North Bengkulu - Sonita, Anisya; Muntahanah, Muntahanah; Darnita, Yulia; Tanjung, Rahman Fadli (Jurnal Komputer, Informasi dan Teknologi, 2022)
In the era of the rapid development of telecommunications, there are many types mobile phones whicht are smart phones on the market. One example that is being widely known in the mobile phone market, many smartphones use Android platform. There are many advantages of android. A café also possible to take advantage of android technology both for customer satisfaction and the benefit of the cafe owner. This study uses the UCD method which conducts interviews with cafe owners or research sites so that they can get results on how the needs, designs and feasibility are as well as tests on the menu selection application. From the results of the research that has been done, it can be concluded that the application is in accordance with the wishes of costumers, and by using the blackbox method it is also in accordance with the wishes of the cafe owner.